Identifying the outcomes important to men with hypogonadism: A qualitative evidence synthesis. (8th February 2022) - Aceves‐Martins, Magaly; Quinton, Richard; Brazzelli, Miriam; Cruickshank, Moira; Manson, Paul; Hudson, Jemma; Oliver, Nick; Hernandez, Rodolfo; Aucott, Lorna; Wu, Frederick; Dhillo, Waljit S.; Bhattacharya, Siladitya; et al.
Abstract: Objective: Men with male hypogonadism (MH) experience sexual dysfunction, which improves with testosterone replacement therapy (TRT). However, randomised controlled trials provide little consensus on functional and behavioural symptoms in hypogonadal men; these are often better captured by qualitative information from individual patient experience. Methods: We systematically searched major electronic databases to identify qualitative data from men with hypogonadism, with or without TRT. Two independent authors performed the selection, extraction, and thematic analysis of data. Quality of eligible studies was assessed using the Critical Appraisals Skills Programme and Grading of Recommendations Assessment, Development and Evaluation‐Confidence in the Evidence from Reviews of Qualitative research tools. Results: We analysed data from five studies published in nine reports that assessed a total of 284 participants. Published data were only available within North America, with no ethnic minority or other underserved groups included. In addition to sexual dysfunction, men with MH experienced adverse changes in physical strength, perceptions of masculinity, cognitive function, and quality of life. The experience of MH appeared dependent on the source(s) of educational material. Discussion: We propose a patient‐centred approach to clinician interactions rather than focusing on discreet MH symptoms. Current evidence about the experience of MH is limited to North America and predominantly white ethnicity, which may not be broadly applicable to other geographic regions. Broadening our understanding of the MH experience may improve the targeting of information to patients. In addition, a multidisciplinary approach may better address symptoms neither attributable to MH nor alleviated by TRT.